2012
DOI: 10.1097/iae.0b013e31821c4087
|View full text |Cite
|
Sign up to set email alerts
|

Transconjunctival Drainage of Serous and Hemorrhagic Choroidal Detachment

Abstract: Transconjunctival drainage of serous and hemorrhagic choroidal detachments seems to be a feasible and simple surgical option with minimal scleral and conjunctival damage. Pars plana vitrectomy may not be necessary when draining choroidal detachments in this manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
0
30
0
2
Order By: Relevance
“…In the past, many surgeons have described the use of vitrectomy instruments for SB, including chandelier lighting and wide-angle viewing systems on surgical microscopes [12,13]. Similarly, the development of new techniques to drain choroidal detachments, using trocars placed in the suprachoroidal space, have allowed surgeons to be more familiarized with this region of the posterior segment [14,15]. SCB uses techniques that are more familiar to vitrectomytrained surgeons, but many are still reticent to try it.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, many surgeons have described the use of vitrectomy instruments for SB, including chandelier lighting and wide-angle viewing systems on surgical microscopes [12,13]. Similarly, the development of new techniques to drain choroidal detachments, using trocars placed in the suprachoroidal space, have allowed surgeons to be more familiarized with this region of the posterior segment [14,15]. SCB uses techniques that are more familiar to vitrectomytrained surgeons, but many are still reticent to try it.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Rezende et al8 evaluated transconjunctival drainage of serous and hemorrhagic choroidal detachment using 20- or 25-gauge transconjunctival trocar/cannula systems. They inserted the transconjunctival trocar/cannula systems into the suprachoroidal space 7.0 mm from the limbus, and reported that vitrectomy may not be necessary when the choroidal detachments are drained in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…7 Rezende et al 8 described the transconjunctival drainage of haemorrhagic choroidal detachments angulation. After entering the cutting tip, only the cannula progresses, thus avoiding iatrogenic retinal damage.…”
Section: Drainage Of Extensive Suprachoroidal Haemorrhagesmentioning
confidence: 99%